(untitled) (Research, Society and Development, 2020)
In learning scenarios, the main focus should be on knowledge about the learner’s strengths and weaknesses. In this context, this article aims to present the results obtained in the previous investigation of the learning styles of teachers in continuing education, in the perspective of the development of strategies that take into account the singularities of the teacher / student. This investigation deals with a case study on teachers in a broad sense in the area of Environmental Education, in a hybrid model, with classroom and virtual environment, offered by a public University. We sought to analyze the responses to promote personalization in the classroom and virtual classroom activities based on pedagogical strategies that included all styles of trainees present. To identify the learning style, an open questionnaire was applied, based on the model by Kolb, where a sample of 57 respondents was obtained, where different learning styles were identified among the course participants. The results indicate that training courses designed for the teaching professional who seek knowledge about the specificities of this professional, using instruments that value and recognize their opinion, favor them to be protagonists of their own training.